PERUBAHAN TATAKELOLA TAMAN NASIONAL: STUDI KASUS DI TAMAN NASIONAL GUNUNG HALIMUN SALAK - Bambang Supriyanto; Hideyuki Kubo; Atih Sundawiati (Department of Forest Resources Conservation and Ecotourism - IPB University, 2010)
Changes in national parks (NP) governance include 1) change in NP management policy which was originally precedence for protection and preservation, now includes real economy for the community, 2) implementation process of the change at field level. This paper discusses the governance change in Gunung Halimun Salak National Park (TNGHS) and its impacts on resource users. Change in governance could take place if the interactive process that occurred between the Head of the National Park, field officers and the community included: (1) Clear and simple policy guidance from the Head of NP on the policy implementation of the new governance be given to field officers, (2) develop relationship between field officers and local community through active interaction. Shift in the implementation technique of NP governance for protection and preservation from